Advanced Flexible CIGS Solar Cells Enhanced by Broadband Nanostructured Antireflection Coatings. Issue 1771 (10th June 2015) - Pethuraja, Gopal G.; Welser, Roger E.; Zeller, John W.; Puri, Yash R.; Sood, Ashok K.; Efstathiadis, Harry; Haldar, Pradeep; Harvey, Jennifer L.
ABSTRACT: Flexible copper indium gallium diselenide (CIGS) solar cells on lightweight substrates can deliver high specific powers. Flexible lightweight CIGS solar cells are also primary candidates for building-integrated panels. In all applications, CIGS cells can greatly benefit from the application of broadband and wide-angle AR coating technology. The AR coatings can significantly improve the transmittance of light over the entire CIGS absorption band spectrum. Increased short-circuit current has been observed after integrating AR coated films onto baseline solar panels. NREL's System Advisor Model (SAM) has predicted up to 14% higher annual power output on AR integrated vertical or building-integrated panels. The combination of lightweight flexible substrates and advanced device designs employing nanostructured optical coatings together have the potential to achieve flexible CIGS modules with enhanced efficiencies and specific power.